The moderating role of dynamic capability between strategic orientations and firm performance in Malaysia agro based SME - Chow, Yeong Kang (2016)
The purpose of this research was to assess the strategic orientations and firm performance in agro-based small and medium enterprises (SMEs). The research focused on SMEs because of their importance in GDP contribution to the Malaysian economy and the high percentage of employment in the labor market. Agro-based SMEs are facing challenges such as the largely aging population; lack of innovation activities, scientific knowledge and application technology as well as less market driven strategies although faced with a large degree of competition from regional countries. The present study aimed to fill the gap between theory and understanding, by investigating the moderating role of dynamic capability (DC) between the relationship of entrepreneurial (EO), learning (LO) and market orientations (MO), as independent variables and agro-based SME firm performance, as the dependent variable. Building on the resourced- based view (RBV), this study theoretically hypothesised a positive relationship between strategic orientations and firm performance. The research methodology included a descriptive analysis, and multivariate and hierarchical regression analysis of the population in the agro-based SMEs. The empirical findings from the cross-sectional quantitative survey of 396 agro-based SME firms in Malaysia revealed that EO and MO were positively related to firm performance, except LO. Dynamic capability had a moderating effect on EO; and MO individually, except LO. Furthermore, dynamic capability had a partial moderating effect on strategic orientations, as a bundle of firm intangible resources on firm performance. This study extends the present theoretical knowledge of dynamic capability, by understanding its moderating role, which influences strategic orientations leading to firm performance. Besides this, the findings of this study provide managerial implications on how dynamic capability playing a strategic role, in outward exploration and inward exploitation through innovation, could improve agro- based SME firm performance. Finally this study identifies a few limitations and recommends further research opportunities